ANALISIS KEMAMPUAN LAHAN UNTUK ARAHAN PENGGUNAAN LAHAN PADA LERENG TIMUR LAUT GUNUNG AGUNG KABUPATEN KARANGASEM-BALI - Budiarta, I Gede; Nuarsa, I Wayan; Adhika, I Made (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science); Vol 9 No 2 (2015), 2015)
This research was conducted in the northeastern slopes of Mount Agung in Karangasem regency, Bali province. The research area is dry land with land use patterns that have not demonstrated compliance with existing land potential. On the other hand, technological advances in the field of agriculture has been growing rapidly, one by analyzing the ability of the land to determine the potential of land resources and minimize the risk of failure of farmers. The results of the analysis of land capability is expected to serve as guidelines in a more optimal use of land in accordance with expectations. The purpose of this study was to determine the potential of land and recommends referral based land use conditions existing land capability in the area of research. The design used is descriptive design, with the main objective to provide a picture or description of land use capability and suitability of the study area. Guidelines for land capability analysis in this study refers to Arsyad (2006) and the Regulation of the Minister of Environment No. 17 Year 2009 on Guidelines for Determining Environmental Carrying Capacity in Regional Spatial Planning. The results showed that 1) land capability class research in areas ranging from class III to class VI. Land capability class III is spread on the land unit 1, land unit 2, land unit 3,and land unit 8. Capability class IV land located on land unit 4, land unit 7, land unit 9, land unit 10 and land unit 12.Land capability classes VI located on land unit 5, land unit 6, and land unit 11; 2) land use suitability value obtained was 92.85%. This shows that almost the entire study area (92.85%) is in conformity between the ability of the land and its use. The rest (7.15%) classified as not appropriate. Suitability of the land use study area into the high criteria; 3) Referral land use adapted to the existing conditions of land units. In class III-IV land that does not meet the user or not used optimally, land use options to do that seasonal crops, plantation crops. While on a class VI land use that is not appropriate or not used optimally, land use options to do that forest production and non-agricultural land use.
Keywords: Classes of land capability, suitability of land use, land-use directives